2019
DOI: 10.1108/ijse-02-2019-0082
|View full text |Cite
|
Sign up to set email alerts
|

Gender longevity gap and socioeconomic indicators in developed countries

Abstract: Purpose The purpose of this paper is to explain relations between socioeconomic factors and gender longevity gap and to test a number of contradicting theories. Design/methodology/approach Fixed effects models are used for cross-country panel data analysis. Findings The authors show that in developed countries (Organization for Economic Cooperation and Development and European Union) a lower gender longevity gap is associated with a higher real GDP per capita, a higher level of urbanization, lower income i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…These further analyzes could provide a more accurate understanding of the epidemiological changes that are leading to variations in lifespan, considering a large and comprehensive set of causes of death. Finally, previous studies of the sex gap in life expectancy have emphasized the importance of social conditions and social change (Fedotenkov & Derkachev, 2019;Luy & Gast, 2014;Mondal & Shitan, 2014;Rogers et al, 2010;Tarkiainen et al, 2012;Thorslund et al, 2013;Trias-Llimós & Janssen, 2018). Hence, future studies should put emphasis on the impact of a broad range of modifiable life style factors and avoidable mortality to understand the ongoing shifts in cause-specific sex gaps in life expectancy, their compression or dispersion, as well as the scope for future improvements.…”
Section: Discussionmentioning
confidence: 98%
“…These further analyzes could provide a more accurate understanding of the epidemiological changes that are leading to variations in lifespan, considering a large and comprehensive set of causes of death. Finally, previous studies of the sex gap in life expectancy have emphasized the importance of social conditions and social change (Fedotenkov & Derkachev, 2019;Luy & Gast, 2014;Mondal & Shitan, 2014;Rogers et al, 2010;Tarkiainen et al, 2012;Thorslund et al, 2013;Trias-Llimós & Janssen, 2018). Hence, future studies should put emphasis on the impact of a broad range of modifiable life style factors and avoidable mortality to understand the ongoing shifts in cause-specific sex gaps in life expectancy, their compression or dispersion, as well as the scope for future improvements.…”
Section: Discussionmentioning
confidence: 98%
“…However, poor health caused by it can apply to both genders in a similar way. Furthermore, Fedotenkov and Derkachev (2019) showed that more work reduces life expectancy. But, according to our study, more work means higher pension and for men it probably could balance the negative effects of work on health and life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, the impact of income differentiation on further life expectancy in terms of gender has not been finally determined. Fedotenkov and Derkachev (2019), for example, show that higher income increases life expectancy both for males and females; however, males' life expectancy is affected to a larger extent. The literature indicates that women could live longer because of men's lifestyles (Cockerham 1997).…”
Section: Introductionmentioning
confidence: 99%